A complex network perspective on interrelations and evolution features of international oil trade, 2002–2013. (15th June 2017) - Du, Ruijin; Wang, Ya; Dong, Gaogao; Tian, Lixin; Liu, Yixiao; Wang, Minggang; Fang, Guochang
Highlights: The top 1 network model can well reflect countries' preference in choosing oil trade partners. The modified closed-system input-output method can reflect the direct and indirect influences among oil trading countries. The interrelation and evolution features of international oil trade network have been discussed. The result shows us how to make a rational decision for a country to develop oil trade relations. Abstract: In this paper, a directed and weighted world crude oil trade network is constructed. Based on the built network, we apply top network method and modified closed-system input-output method to assess the relative importance of countries in the international oil trade. The top 1 network consisting of top trade relations, can well reflect countries' preference in choosing oil trade partners. As a simplified network model of international oil trade network, the top 1 network has been analyzed the structure and evolution. In order to identify important oil trading countries, the modified closed-system input-output analysis has yielded some promising results, which show countries who play key role in international oil trade, are trading large oil volumes. In addition, by describing the influences of countries on each other, we find major oil importers have a much effect on other countries, including major oil exporters. The evolution analysis obtained by these two methods coincide with each other. To conclude, some suggestions are given according to the results.